2013
DOI: 10.1152/ajpcell.00280.2012
|View full text |Cite
|
Sign up to set email alerts
|

SMB myosin heavy chain knockout enhances tonic contraction and reduces the rate of force generation in ileum and stomach antrum

Abstract: The role of SMA and SMB smooth muscle myosin heavy chain (MHC) isoforms in tonic and phasic contractions was studied in phasic (longitudinal ileum and stomach circular antrum) and tonic (stomach circular fundus) smooth muscle tissues of SMB knockout mice. Knocking out the SMB MHC gene eliminated SMB MHC protein expression and resulted in upregulation of the SMA MHC protein without altering the total MHC protein level. Switching from SMB to SMA MHC protein expression decreased the rate of the force transient an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Consistent with the inhibition of sustained contraction by Y27632, treatment of cultured muscle cells for 10 min with ACh induced phosphorylation of MYPT1 at Thr 696 and MLC 20 at Ser 19 ; phosphorylation of both MYPT1 and MLC 20 was blocked by LARG siRNA (Fig. 5C).…”
Section: Distinctive Pattern Of Activation Of G Proteins By Muscarinisupporting
confidence: 78%
See 1 more Smart Citation
“…Consistent with the inhibition of sustained contraction by Y27632, treatment of cultured muscle cells for 10 min with ACh induced phosphorylation of MYPT1 at Thr 696 and MLC 20 at Ser 19 ; phosphorylation of both MYPT1 and MLC 20 was blocked by LARG siRNA (Fig. 5C).…”
Section: Distinctive Pattern Of Activation Of G Proteins By Muscarinisupporting
confidence: 78%
“…Functional differences are evident between muscle layers (e.g., circular vs. longitudinal muscle of the intestine) or within the same layer (proximal tonic vs. distal rhythmic circular muscle of the stomach) (10,19,31,35,38,58,59). In all types of smooth muscle, an essential requirement for contraction is phosphorylation of the 20-kDa regulatory light chain (MLC) of myosin II (MLC 20 ), which in turn is regulated by the balance between Ca 2ϩ -dependent or -independent MLC kinase (MLCK) activity and MLC phosphatase (MLCP) activity (8,13,25,37,55).…”
mentioning
confidence: 99%
“…The phasic and tonic behavior of smooth muscles may be related to differences in content and isoform composition of contractile proteins and intracellular signaling molecules that regulate the activities of MLCK and MLC phosphatase (4,6,7,13,15,17,(21)(22)(23)(24)36). For example, previous studies have shown that phasic muscle differs from the tonic muscle in the relative abundance of the ratio of acidic to basic isoforms of the 17-kDa essential light chain, in the ratio of seven-amino acid inserted to noninserted myosin heavy chain isoforms (SMA/ SMB isoforms) (2,17,21), in thin-filament-associated proteins such as caldesmon and calponin, and in the signaling pathways that regulate MLC 20 phosphorylation (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies have shown that phasic muscle differs from the tonic muscle in the relative abundance of the ratio of acidic to basic isoforms of the 17-kDa essential light chain, in the ratio of seven-amino acid inserted to noninserted myosin heavy chain isoforms (SMA/ SMB isoforms) (2,17,21), in thin-filament-associated proteins such as caldesmon and calponin, and in the signaling pathways that regulate MLC 20 phosphorylation (45,46). These differences in the expression of contractile proteins and biochemical pathways highly correlate with the functional phasic phenotype of antrum and tonic phenotype of fundus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation